PENGARUH STRATEGI PEMASARAN PRODUK TABAH (TABUNGAN MUDHARABAH) TERHADAP MINAT NASABAH DI KSPPS BMT NU JAWA TIMUR CAB. SOCAH BANGKALAN - Fatmawati, Iis; Himmah, Aliyatul; Mufaizin (LPPM Sekolah Tinggi Agama Islam Al-Utsmani Bondowoso, 2023)
The development of the times is increasingly rapid with the existence of technology that continues to run dynamically. This does not close efforts to upgrade human resources and products in banking to attract customers. The creation of superior human resources with the right strategy makes its own points for a financial institution. In addition, the existence of a good strategy is of course based on field data and also surveys in advance about what and how consumers want to be interested in a product. This study aims to determine the influence of Tabah marketing strategy (Mudharabah Savings) on Customer Interest at KSPPS BMT NU Socah Bangkalan Branch. This type of research is a simple quantitative linear regression with a sample of 24 respondents, using, using a Likert scale, with a sampling technique, namely Propability Sampling with a type of Simple Random Sampling. Based on the results of the study, the discussion shows that the independent variable has a significant influence on the dependent variable. This can be seen from the results of the Tcount Test 2,726 greater than the significant level of 0.05. Keywords: Steadfast Marketing Strategy, Customer Interest